Current status of glucose, blood pressure and lipid management in type 2 diabetes clinic attendees in Isfahan, Iran. Issue 6 (17th April 2015) - Janghorbani, Mohsen; Papi, Bahman; Amini, Masoud
Abstract Aims/Introduction To estimate the prevalence of meeting American Diabetes Association clinical practice recommendations for hemoglobin A1c (HbA1c), blood pressure (BP) and low‐density lipoprotein cholesterol (LDLC) among Iranian type 2 diabetes clinic attendees, and to identify the factors associated with therapeutic target achievement. Materials and Methods A total of 2, 640 patients with type 2 diabetes (944 men and 1, 696 women) from Isfahan Endocrine and Metabolism Research Center outpatient clinics, Iran, were examined. The main outcome measures were HbA1c, BP and LDLC, in accordance with the American Diabetes Association recommendations. The mean (standard deviation) age of participants was 49.6 years (9.3 years) with a mean (standard deviation) duration of diabetes of 5.0 years (4.9 years) at initial registration. Results The percentages of patients who had HbA1c <7%, BP <140/90 mmHg and LDLC <100 mg/dL was 37.4% (95% confidence interval [CI] 35.6–39.3), 35.3% (95% CI 33.5–37.3) and 48.9% (95% CI 47.0–50.8), respectively. The proportion of patients meeting all three goals was 7.7% (95% CI 6.7–8.8). Lower BP, cholesterol level and higher education at registration, and higher follow up but lower number of follow‐up visits affected achievement of all three goals. Conclusions The present study highlights that a substantial proportion of Iranian type 2 diabetes clinic attendees did not meet the American Diabetes Association clinical practice recommendations, and shows the difficult challenges physicians face when treating patients with type 2 diabetes.